2004
DOI: 10.1128/aem.70.5.3091-3095.2004
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Respiration by Geobacter metallireducens : Novel Strategy for In Situ Removal of Vanadium from Groundwater

Abstract: Vanadium can be an important contaminant in groundwaters impacted by mining activities. In order to determine if microorganisms of the Geobacteraceae, the predominant dissimilatory metal reducers in many subsurface environments, were capable of reducing vanadium(V), Geobacter metallireducens was inoculated into a medium in which acetate was the electron donor and vanadium(V) was the sole electron acceptor. Reduction of vanadium(V) resulted in the production of vanadium(IV), which subsequently precipitated. Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
121
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(128 citation statements)
references
References 27 publications
(31 reference statements)
6
121
0
1
Order By: Relevance
“…Geobacter species are important agents in the bioremediation of organic contaminants (Lovley et al, 1989;Rooney-Varga et al, 1999;Lin et al, 2005), as well as uranium (Anderson et al, 2003;North et al, 2004;Vrionis et al, 2005) and vanadium (Ortiz-Bernad et al, 2004b). Analysis of gene transcript abundance within the subsurface Geobacter community has been successful in diagnosing rates of metabolism in Geobacter species as well as nutrient limitations and stress responses (Holmes et al, 2004b(Holmes et al, , 2005O'Neil et al, 2008;Mouser et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Geobacter species are important agents in the bioremediation of organic contaminants (Lovley et al, 1989;Rooney-Varga et al, 1999;Lin et al, 2005), as well as uranium (Anderson et al, 2003;North et al, 2004;Vrionis et al, 2005) and vanadium (Ortiz-Bernad et al, 2004b). Analysis of gene transcript abundance within the subsurface Geobacter community has been successful in diagnosing rates of metabolism in Geobacter species as well as nutrient limitations and stress responses (Holmes et al, 2004b(Holmes et al, , 2005O'Neil et al, 2008;Mouser et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…They have been found to be ubiquitous in a myriad of subsurface environments. Detailed studies of their metabolism have revealed them to be capable of bioremediation of several heavy metals, including uranium, plutonium, technetium, and vanadium, as well as biodegradation of several organic contaminants, including monoaromatic hydrocarbons (16,17,26). More recently, Geobacter species have been used to generate electricity from waste organic matter (2, 15, 19).…”
mentioning
confidence: 99%
“…V (V) reduction was observed during field experiments at Old Rifle and has been shown to be mediated by iron reducing bacteria (Ortiz-Bernad et al, 2004). However, in these simulations we elected to ignore growth via V (V) reduction as there is considerable uncertainty in the chemical speciation of vanadium in groundwater at the Old Rifle site and this precluded our developing realistic growth equations for this process.…”
Section: Reaction Path Calculationsmentioning
confidence: 99%